Assessing photosynthetic performance of fennel (Foeniculum vulgare Mill) influenced by plant growth regulators and drought stress imposed at vegetative and reproductive stages - Parmoon, Ghasem; Ebadi, Ali; Jahanbakhsh, Soodabeh; Hashemi, Masoud; Moosavi, Seyed Amir (Italian Journal of Agronomy, 2019)
Maintaining crop productivity under limited irrigation water requires some new strategies. This study investigated the influence of drought stress and the application of plant growth regulators (PGRs) including jasmonic acid, brassinosteroids, and putrescine on photosynthetic performance of fennel (Foeniculum vulgare Mill). The results indicated that fennel exhibited active osmoregulation which prevented a sharp decrease in relative water content. Fennel successfully maintained high leaf chlorophyll index, Net photosynthesis rate, and transpiration under mild stress, however, severe stress reduced the photosynthetic parameters by 22%, 24%, and 50%, respectively. Drought stress increased chlorophyll a fluorescence when fennel plants exposed to the stress condition. Vk and Wk parameters related to the donor side of photoinhibition of photosystem II (PSII) increased by 44% when severe drought stress imposed at the vegetative stage and 34% when occurred during the flowering. The elevation of Vk and Wk indicated a failure in water splitting in PSII. The VJ and VI parameters of acceptor sides increased by 16% and 22%, respectively when drought stress imposed at the vegetative phase and to 19% and 30%, when drought stress occurred during reproductive phase. Using PGRs resulted in reduced VJ, VI, Vk, and Wk, suggesting that some degree of recovery of damages occurred. All three PGRs stimulated biomass production and on average, plants yielded roughly 1.6 fold higher than the control plants. The influences of PGRs were mainly independent of drought stress level.